Circulating nesfatin-1 levels in women with polycystic ovary syndrome: A systematic review and meta-analysis - Seyed Sobhan Bahreiny; Akram Ahangarpour; Ali Asghar Hemmati; Razieh Kazemzadeh; Mohammad-Navid Bastani; Mohammad Reza Dabbagh; Mojtaba Aghaei (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder in females. Nesfatin-1 is a neuropeptide synthesized in the hypothalamus and other peripheral organs, and there are conflicting opinions about its correlation with PCOS. Objective: This study aims to investigate the correlation between nesfatin-1 and PCOS and evaluates the effectiveness of nesfatin-1 as a biomarker for the detection of PCOS in women. Materials and Methods: A systematic review and meta-analysis were conducted to identify pertinent articles from databases such as PubMed, Web of Science, Cochrane, EMBASE, Scopus, and Google Scholar. The standardized mean difference (SMD) and 95% confidence interval (CI) were calculated using a random effects model to compare group outcomes. Additionally, meta-regression and subgroup analysis were performed to elucidate sources of heterogeneity. Results: The meta-analysis involved 12 studies with 1222 participants, and the findings revealed a significant relationship between PCOS and nesfatin-1 levels. The pooled (SMD = 0.54; 95% CI: 0.00-1.07; p = 0.04) indicated a significant difference between the evaluated groups. Moreover, a subgroup analysis showed that there was a substantial difference in nesfatin-1 levels among women with PCOS and higher homeostatic model assessment for insulin resistance ratio (SMD = 1.46; 95% CI: 0.92-2.00; p < 0.001). Conclusion: Our meta-analysis indicates an association between high nesfatin-1 levels and PCOS. This suggests a potential role of nesfatin-1 in the development of PCOS and proposes it as a potential diagnostic biomarker for the disease. However, further research is necessary to validate these findings.